The Role of Trust in the Relationship between Past Interactions and Buying Intention in Virtual Organizations - Dwi Kurniawan; Sabila Rafa Budiyanto (International Journal of Industrial Engineering and Production Research)
This paper studied the impact of relationships and past positive experiences on the dimensions of trust (ability, benevolence, integrity) and the influence of these trust dimensions on customer purchase intention. The measurement instrument was developed based on the literature. The study was conducted using a questionnaire completed by two hundred customers of an Indonesian Marketplace in Bandung and its surrounding areas. The data were then processed using Structural Equation Modeling (SEM). The results showed that ability and integrity affect customer purchase intentions, while benevolence does not. Additionally, we found that relationships and positive experiences in the past significantly affect ability and integrity.